2006
DOI: 10.1186/1472-6874-6-12
|View full text |Cite
|
Sign up to set email alerts
|

Counselling and knowledge about contraceptive mode of action among married women; a cross-sectional study

Abstract: BackgroundFamily planning counselling which covers knowledge transfer about contraceptive mode of action, by enabling informed choice, improves compliance to and efficiency of contraceptive methods.The objective of this study was to investigate associations between family planning counselling, counsellor and correct knowledge about mode of action of modern contraceptive methods among married women.MethodsFor this cross-sectional study, stratified (according to current modern contraceptive method in use) random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 11 publications
(10 reference statements)
0
10
0
5
Order By: Relevance
“…In the Topsever et al study [24], having a high education level was shown to be significantly associated with knowing the mode of action of the contraceptive method used (OR=3.02, 95%CI=1.99-4.58). In addition, they found that knowledge about non-barrier methods such as hormonal methods, IUDs, or sterilization was lower than knowledge of barrier methods, even among highly educated women [24]. Heimberger et al [32] also revealed that more education was significantly associated with better knowledge of EC among clients of FP clinics in Mexico.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the Topsever et al study [24], having a high education level was shown to be significantly associated with knowing the mode of action of the contraceptive method used (OR=3.02, 95%CI=1.99-4.58). In addition, they found that knowledge about non-barrier methods such as hormonal methods, IUDs, or sterilization was lower than knowledge of barrier methods, even among highly educated women [24]. Heimberger et al [32] also revealed that more education was significantly associated with better knowledge of EC among clients of FP clinics in Mexico.…”
Section: Discussionmentioning
confidence: 91%
“…A study conducted among Turkish women from primary health centers found that only 33.6% of barrier methods users and 5.7% of non-barrier methods users had correct knowledge about how their current method worked. It was not specified in the article what "correct knowledge" was for each method [24]. Another study, exploring beliefs about EC among female patients at two academic family medicine clinics in the USA, found that 24% of women responded that EC pill worked before fertilization, 36% before implantation, 6%…”
Section: Discussionmentioning
confidence: 99%
“…In study conducted by Topsever P et al, 41.9% of the women of reproductive age in Degirmendere were using a modern contraceptive method. 4 The condom method was favoured by most of participants of the present study (49.1%).…”
Section: Resultsmentioning
confidence: 62%
“…Wanita berpendidikan lebih tinggi secara bermakna lebih mungkin mengetahui metode kontrasepsi yang digunakan. 10 Penggunaan alat pengambilan keputusan oleh penyedia kesehatan, dan pemberian informasi tentang keluarga berencana, menunjukkan keterlibatan pasien dalam proses pengambilan keputusan. Komunikasi pasien menjadi meningkat serta kontribusi tenaga kesehatan mengalami pergeseran yang didominasi pada penerapan model shared decision making.…”
Section: Pendahuluanunclassified
“…12,13 Seperti yang dinyatakan penelitian sebelumnya, banyak cara meningkatkan kualitas pelayanan keluarga berencana antara lain meningkatkan dan mempertahankan hubungan terapeutik antara pasien dan petugas kesehatan, meningkatkan komunikasi dan memperbaiki alat bantu pengambilan keputusan MKJP. 10 Semua unsur tersebut telah ada dalam shared decision making model yang menjalankan kegiatan konseling. Bentuk komunikasi interpersonal khusus membantu membuat keputusan atau memecahkan masalah melalui pemahaman klien meliputi faktafakta, harapan, kebutuhan, dan perasaan klien merupakan kegiatan konseling.…”
Section: Penerapan Shared Decision Making Modelunclassified